Cytogenetic and genomic analysis of a patient with turner syndrome and t(2;12): a case report - Paola E. Leone; Verónica Yumiceba; Ariana Jijón-Vergara; Andy Pérez-Villa; Isaac Armendáriz-Castillo; Jennyfer M. García-Cárdenas; Santiago Guerrero; Patricia Guevara-Ramírez; Andrés López-Cortés; Ana K. Zambrano; Jesús M. Hernández-Rivas; Juan Luis García; et al. (Molecular Cytogenetics, 2020)
Abstract Background Turner syndrome is a genetic disorder that affects women. It is caused by an absent or incomplete X chromosome, which can be presented in mosaicism or not. There are 12 cases of Turner syndrome patients who present structural alterations in autosomal chromosomes. Case presentation The present case report describes a patient with a reciprocal, maternally inherited translocation between chromosomes 2 and 12 with a mosaicism of X monosomy 45,X,t(2;12)(p13;q24)[95]/46,XX,t(2;12)(p13;q24)[5]. Through genetic mapping arrays, altered genes in the patient were determined within the 23 chromosome pairs. These genes were associated with the patient’s clinical features using a bioinformatics tool. Conclusion To our knowledge, this is the first case in which a translocation (2;12) is reported in a patient with Turner syndrome and confirmed by conventional cytogenetics, FISH and molecular genetics. Clinical features of our patient are closely related with the loss of one X chromosome, however mild intellectual disability can be likely explained by autosomal genes. The presence of familial translocations was a common finding, thus emphasizing the need for familiar testing for further genetic counselling.